Penanaman Karakter Peduli Sosial Pada Siswa Sekolah Dasar - Muhamad Arif; Jesica Dwi Rahmayanti; Fitri Diah Rahmawati (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2021)
The character of social care is one of the characters that must be developed in the State of Indonesia, strengthening the character (character) in students must be done optimally so that it supports in strengthening the national identity that cares regardless of race and culture or even religion. Several cases of the lack of social care around the community, as Tabi'in explained that the all-digital era encourages individualism, this can be seen when an incident occurs, such as when a friend or other person falls (hit by a disaster), the first thing to do is not help him. However, on the contrary, some individuals are more busy capturing these moments by taking pictures or sharing on social media networks. This study used a qualitative method with an empirical background case study approach at the Muhammadiyah 1 Menganti Gresik Elementary School. The primary data sources in this study were class teachers ranging from grades 1-6. Methods of data collection using participatory observation, semi-structured interviews and documentation at the Muhammadiyah 1 Menganti Gresik Elementary School. In the process of collecting data, researchers used data analysis techniques from Miles and Hubarman, data condensation, display data and recording conclusions. The process of cultivating the character of social care in students, there are two stages carried out by the Muhammadiyah 1 Menganti Gresik Elementary School. First, is the example of the teacher. Second, is habituation that must be carried out continuously. Meanwhile, in strengthening the two stages, Muhammadiyah 1 Menganti Gresik Elementary School, several programs, namely: philanthropy, takjil on the road, donations for victims of natural disasters, social services, distribution of qurban meat and qurban for food safety.